2015
DOI: 10.1007/s12034-015-1009-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heat treatment temperature on bonding and oxidation resistance of diamond particles coated with TiO2 film

Abstract: In this paper, TiO 2 films were coated on the surface of diamond particles using a sol-gel method. The effects of heat treatment temperature on the morphology, composition, chemical bonds, oxidation resistance and compressive strength of diamond particles coated with TiO 2 films were characterized through scanning electron microscopy, Fourier transform infrared, Raman spectroscopy, X-ray diffraction analysis, X-ray photoelectron spectroscopy, thermogravimetric-differential scanning calorimetry and compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Usually, the D band is positioned at 1325 cm −1 . However, a shift of approximately 35 cm −1 was found in the Raman spectrum, which was attributed to the formation of the TiOC bond . It was also observed that the disordered carbon peaks had significantly decreased with the increased exposure power, which was explained by the oxidation of the carbon species under high laser fluency in the presence of oxygen from air.…”
mentioning
confidence: 99%
“…Usually, the D band is positioned at 1325 cm −1 . However, a shift of approximately 35 cm −1 was found in the Raman spectrum, which was attributed to the formation of the TiOC bond . It was also observed that the disordered carbon peaks had significantly decreased with the increased exposure power, which was explained by the oxidation of the carbon species under high laser fluency in the presence of oxygen from air.…”
mentioning
confidence: 99%